Characteristics Of Saddang River Sand, Pinrang Regency, South Sulawesi, Indonesia Based On Grain Gradation, Mud Content And Specific Gravity - Arsyad; Arifin, Moch. Aris; Mukrim, Muh. Ihsan; Jamaluddin; Hamzah; Rauf, Abd.; Bauna, Ruslan; Reno; Nurhikmah; Abdul Latif (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
The research aims to determine the characteristics of sand grain gradation, mud content and specific gravity of Saddang River sand. Saddang river sand is the main source of sand used in construction activities in South Sulawesi and West Sulawesi. In order to ensure that Saddang river sand meets the quality standards used in the construction world, it is necessary to conduct research related to Gradation of grains, mud content and specific gravity of sand. These three factors are part of the factors that determine the quality of concrete and cement mixtures. The research was located at the Saddang River sand mine in Pincara Village, Patampanua subdistrict, Pinrang Regency, South Sulawesi, Indonesia. The research method uses field surveys and laboratory analysis to analyze the gradation of sand grains, mud content and specific gravity. The results of the sieve analysis show that the Saddang River sand is classified as gradation zone no. 4 or classified as fine sand based on the fine aggregate gradation table SNI 03-2834-2000 and ASTM C-33. The results of the analysis of the Saddang River sand mud content ranged from 2.233% to 2.250%, fulfilling SNI 03-4804-1998 which has been determined at a maximum of 5%. The specific gravity analysis show the average value of bulk specific gravity (2,489 gr/m3), dry specific gravity (2,524 gr/m3), and visible specific gravity (2,600 gr/m3). meets SNI 03-1970-2008 standards ranging from < 1.6 gr/m3 to 3.2 gr/m3. The ater absorption in fine aggregate ranged from 1.5% to 3.8%, meeting SNI 03-1970-2008 with a maximum of 5%.